9A.05: SYMPATHETIC NERVOUS SYSTEM DRIVES RENAL INFLAMMATION BY ALPHA(2A)-ADRENOCEPTORS. (June 2015) - Hoch, H.; Hering, L.; Crowley, S.; Zhang, J.; Yang, G.; Rump, L.C.; Vonend, O.; Stegbauer, J.
Abstract : Objective: Inflammatory processes play a pivotal role in pathogenesis of chronic kidney disease (CKD). alpha2A-adrenoceptors (alpha2A-AR) in adrenergic neurons are known for regulating sympathetic tone by controlling norepinephrine (NE) release from sympathetic nerve endings by a negative feedback mechanism. Increased sympathetic tone leads to hypertension and the progression of CKD. In addition, there is some evidence that alpha2A-ARs on non-adrenergic cells have modulating effects on the inflammatory response. Here, we tested our hypothesis that deletion of alpha2A-AR exaggerates renal fibrosis. Design and method: Unilateral ureteral obstruction (UUO), a model of renal fibrosis, was performed in FVB mice lacking the alpha2A-AR (KO) and compared to its wild-type (WT). Renal NE tissue content was measured by HPLC. Immunohistochemistry and gene expression analysis were performed 7 days after UUO. Murine macrophages were isolated from the peritoneal cavity, subsequently cultured and stimulated. Results: Renal sympathetic neurotransmission and NE tissue content was significantly exaggerated in KO compared to WT. Despite an increased sympathetic activity, renal fibrosis, assessed by sirius red/ fast green collagen staining (p = 0.0428) and renal collagen-1 expression (p = 0.001), was significantly attenuated in KO compared to WT 7 days after UUO. Moreover, the expression of the pro-inflammatory and pro-fibrotic cytokines TNF-alpha (p < 0.05) and TGF-beta (p < 0.05), as well as the chemokines CCL2 (p < 0.05) and CCL5 (p < 0.05) were significantly reduced in mice lacking the alpha2A-AR compared to WT indicating a pro-inflammatory role of alpha2A-AR on immune cells in the progression of renal fibrosis. In addition, F4/80-staining confirmed the reduced renal infiltration of macrophages in KO. Stimulation of isolated murine peritoneal macrophages from WT mice with the alpha2-AR-agonist UK14.304 (0.1 μM) induced a 2-fold expression of TNF-alpha (p < 0.05). Conclusions: Alpha2A-ARs appear not only to be a key player in regulating sympathetic tone, but also promote inflammation and the progression of renal fibrosis in response to kidney injury. To dissect the cell type and whether adrenergic or non-adrenergic alpha2A-ARs are responsible for these effects further experiments are necessary. Experiments with a transgenic mouse re-expressing the adrenergic alpha2A-ARs are planned. First results give an idea that non-adrenergic alpha2A-ARs could responsible for the observed effects.